Studi Preferensi Masyarakat Jakarta Terhadap Genderless Fashion - Nadiah Salsabila Hakim Pambudi; Achmad Haldani; Gregorius Prasetyo Adhitama (JURNAL RUPA, 2019)
The evolution of clothing style always repetitive, one of them is genderless fashion. In Indonesia, especially in Jakarta, genderless clothing is not exposed too much to the public. This research aims to find the meaning of genderless fashion which often indentify as androgyne fashion and people’s preference for genderless fashion. This research collects data through a literature review as well as using questionnaires to find out the preferences of the Jakarta people towards genderless fashion. According to data analysis, it can be interpreted that genderless fashion is a designing process for clothing without any specific gender orientation. The difference lies in one’s physical character, the concept of androgyne fashion is for individuals who has male and female characteristic. The results of questionnaires regarding the preferences are most people know the meaning of genderless fashion and this phenomenon can be accepted in society. However, there are limits that cannot be accepted yet, such as clothes with feminine silhouette and very bright colors. This research intended to be able to rectify public confusion over understanding genderless fashion and androgyne fashion as well as a source of knowledge for designer who wants to know the limitation and acceptence rate for genderless fashion in Jakarta.